Maternal and perinatal factors associated with hospitalised infectious mononucleosis in children, adolescents and young adults: record linkage study. - Mahmud, I; Abdel-Mannan, O; Wotton, C; Goldacre, M (BioMed Central, 2011)
BACKGROUND: There is current interest in the role of perinatal factors in the aetiology of diseases that occur later in life. Infectious mononucleosis (IM) can follow late primary infection with Epstein-Barr virus (EBV), and has been shown to increase the risk of multiple sclerosis and Hodgkin's disease. Little is known about maternal or perinatal factors associated with IM or its sequelae. METHODS: We investigated perinatal risk factors for hospitalised IM using a prospective record-linkage study in a population in the south of England. The dataset used, the Oxford record linkage study (ORLS), includes abstracts of birth registrations, maternities and in-patient hospital records, including day case care, for all subjects in a defined geographical area. From these sources, we identified cases of hospitalised IM up to the age of 30 years in people for whom the ORLS had a maternity record; and we compared perinatal factors in their pregnancy with those in the pregnancy of children who had no hospital record of IM. RESULTS: Our data showed a significant association between hospitalised IM and lower social class (p = 0.02), a higher risk of hospitalised IM in children of married rather than single mothers (p < 0.001), and, of marginal statistical significance, an association with singleton birth (p = 0.06). The ratio of observed to expected cases of hospitalised IM in each season was 0.95 in winter, 1.02 in spring, 1.02 in summer and 1.00 in autumn. The chi-square test for seasonality, with a value of 0.8, was not significant.Other factors studied, including low birth weight, short gestational age, maternal smoking, late age at motherhood, did not increase the risk of subsequent hospitalised IM. CONCLUSIONS: Because of the increasing tendency of women to postpone childbearing, it is useful to know that older age at motherhood is not associated with an increased risk of hospitalised IM in their children. We have no explanation for the finding that children of married women had a higher risk of IM than those of single mothers. Though highly significant, it may nonetheless be a chance finding. We found no evidence that such perinatal factors as birth weight and gestational age, or season of birth, were associated with the risk of hospitalised IM.